Pengaruh Promosi dan Fasilitas terhadap Keputusan Siswa Memilih Sekolah di SMA Nusantara Plus - Rahman Nurhakim; Muhammad Tafsiruddin (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
This study aims to determine the influence and relationship between the variables of promotion and facilities on students' decision to choose a school at SMAS Nusantara Plus. The study was conducted on a population of 89 students of class X as new students. The analysis conducted in this study were hypothesis testing, multiple linear regression, coefficient of determination analysis, and ANOVA. Statistical testing was carried out using the IBM SPSS 25 tool. The results of the study showed that there was a positive influence of the variables of promotion and facilities, either partially or simultaneously, on the decision to choose. Based on the regression results, promotion had a greater influence to the decision than facilities. The determination of the variables of promotion and facilities together to the decision to choose was 61.3%, and the remaining 38.7% was influenced by factors that were not included in this study.